Variabel yang Memengaruhi Risiko Perceraian di Kabupaten Cilacap Tahun 202 - Adima Lu'lu'atun Nabila Munawardani; Suryanto Aloysius (Politeknik Statistika STIS, 2022)
A family from legal marriage is an important foundation in the development of human resources. However, this sometimes cannot be achieved when marriage ends in divorce. This because divorce causes various negative impacts and mainly affects children as the next generation of the nation. Cilacap Regency is the largest contributor to divorce in Central Java with the number of divorces in 2021 reaching 7234 cases. This study aims to determine the general characteristics and variables that affect the risk of divorce in Cilacap Regency in 2021. The data used are secondary data from divorce cases that have been decided by the Cilacap Religion Court in 2021. The analytical method used is survival analysis with parametric method using weibull distribution. The results showed that wife's occupation, husband's education level, wife's education level, place of residence and children had a significant effect on the risk of divorce in Cilacap Regency in 2021.